The Impact of Federal Overtime Legislation on Public Sector Labor Markets - Johnson IV, John H. (Journal of Labor Economics, 2003)
In this article, I provide both econometric and case study evidence on the labor market effects of the U.S. Supreme Court’s 1985 Garcia v. San Antonio Metropolitan Transit Authority decision that made 80% of state and local government workers eligible to receive compensation for overtime hours worked. Empirical evidence suggests that the behavior of public sector workers is consistent with a Coasian model in which overtime provisions are explicitly bargained for by the parties involved, likely making overtime legislation an ineffective tool for influencing the amount of overtime hours worked by public sector employees.